Co‐encapsulation of resveratrol and epigallocatechin gallate in low methoxyl pectin‐coated liposomes with great stability in orange juice. (29th August 2019) - Feng, Simin; Sun, Yuxin; Wang, Pei; Sun, Peilong; Ritzoulis, Christos; Shao, Ping
Summary: To improve long‐term stability of the liposomes, resveratrol (RES) liposomes, epigallocatechin gallate (EGCG) liposomes, RES+EGCG liposomes, RES+EGCG liposomes coated with low methoxyl pectin (LMP) were prepared, and their physical properties were evaluated. The prepared liposomes have a particle sizes of about 110– 160 nm. The LMP‐coated composite liposomes have the largest particle size and zeta potential, the latter indicating higher system stability. Liposome systems were pasteurised and placed in an orange juice system as to study liposome stability in a real the food environment. LMP bridge with metal ions forming a network‐like gel in the LMP‐coated composite liposomes, thereby enhancing the stability of liposomes. LMP‐decorated liposomes could be developed as a formulation for encapsulating and delivering functional ingredients. Abstract : To improve long‐term stability of the liposomes, resveratrol (RES) liposomes, epigallocatechin gallate (EGCG) liposomes, RES+EGCG liposomes, RES+EGCG liposomes coated with low methoxyl pectin (LMP) were prepared, and their physical properties were evaluated. Compared to other liposomes, LMP‐coated complex liposome was more stable and have greater antioxidant effects after pasteurization, and maintain the best sustained release efficiency.